Análise do nível de resiliência, auto-eficácia e motivação entre bailarinos alunos e profissionais - Lazier-Leão, Tatyanne Roiek (2016)
This work presents psychological variables of students and professional dancers. It is a cross-sectional, correlational and descriptive study. They have as general objective to analyze the psychological variables, resilience, self-efficacy and motivation in professional dancers and students considering the different groups. Specific objectives were also listed, being they; To identify the levels of resilience, self-efficacy and motivation of professional dancers and students; Identify dancers with similar psychological characteristics, considering the different groups; To correlate the levels of resilience, self-efficacy, motivation among dancers with similar psychological characteristics. This study included 112 students from the Dance School of the Guaíra Theater, 15 professional ballet dancers from the Teatro Guaíra Ballet and 08 professional dancers from the G2 Cia de Dança, totaling 135 dancers. The evaluation of the psychological variables was performed through four questionnaires, Wagnild and Young's Resilience Scale (1993), Schwarzer and Jerusalem Perceived General Self-Efficacy Scale (1995), Self-Efficacy Scale for Silva Dancers, Luz , Afonso and Araújo (2015), Motivation Scale for Sport II validity by Nascimento Junir et al. (2014). For the data analysis we used: frequency analysis, Kuskall Wallis, Hierarchical Cluster Analysis with Ward's method, ANOVA and Mann-Whitney, Spearmann's correlation, and Pearson's correlation quality were measured according to the criteria of Landis And Koch (1977). The results indicate that Professionals and Students have less Selfconfidence, ability to adapt to situations, high level of physical and psychological selfefficacy. The group of dancers who have similar characteristics are divided into 3 Clusters, "Predominant", "Intermediate" and "Minority", while the group of professional dancers are divided into two groups "Versado" and "Experiente". The results showed that professional dancers and students present high resilience values that show factors such as friendship, personal fulfillment, satisfaction and meaning of life, physical and psychological self-efficacy. In addition, students in the "Predominant" group presented higher values than others, both in the already presented and in resilience dimensions such as independence and determination, perceived general self-efficacy and intrinsic and extrinsic motivation. The "Minority" group was the one that most resembled the other groups. And the group "Intermediate" was the one that obtained smaller values in the majority of the evaluated dimensions. The professionals stood out with high values of resilience as to factors that independence and determination. The "Versado" group presented low physical self-efficacy, while the "Experienced" group reached high values in this dimension. The age of the groups of professional dancers deserves to be highlighted, due to the fact that the "Versado" group had a median well above the "Experienced" group. We found a large number of significant correlations, both positive and negative, in the study we highlight those with moderate and strong correlations. In the group of students resilience reached the highest number of significant correlations, while in the group of professionals was the motivation. It was concluded that students and professionals of the dance present high values among some of the dimensions of the psychological variables of resilience, self-efficacy and motivation. The results also allow us to affirm that dance plays an important role in the construction of a positive psychological profile.